Single‐Domain Ferromagnet of Noncentrosymmetric Uniaxial Magnetic Ions and Magnetoelectric Interaction. Issue 34 (25th April 2017) - Koo, Hyun‐Joo; Gordon, Elijah E.; Whangbo, Myung‐Hwan
Abstract: The feasibility of a single‐domain ferromagnet based on uniaxial magnetic ions was examined. For a noncentrosymmetric uniaxial magnetic ion of magnetic momentμ at a site of local electric dipole momentp, it is unknown to date whetherμ prefers to be parallel or antiparallel toμ . The nature of this magnetoelectric interaction was probed in terms of analogical reasoning based on the Rashba effect and density functional theory (DFT) calculations. We show thatμ andp prefer an antiparallel arrangement, predict that Fe‐doped CaZnOS is a single‐domain ferromagnet like a bar magnet, and find the probable cause for the ferromagnetism and weak magnetization hysteresis in Fe‐doped hexagonal ZnO and ZnS at very low dopant concentrations. Abstract : The feasibility of a single‐domain ferromagnet of uniaxial magnetic ions is explored, as is the nature of the magnetoelectric interaction for a noncentrosymmetric uniaxial magnetic ion, and the cause for ferromagnetism and weak magnetization hysteresis in Fe‐doped hexagonal ZnO and ZnS.